2015
DOI: 10.1016/j.jse.2015.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Alteration and recovery of arm usage in daily activities after rotator cuff surgery

Abstract: This study provided new information on arm recovery after rotator cuff surgery using an innovative measurement method. It highlighted that objective arm underuse measurement is a valuable indicator of upper limb postsurgical outcome that captures a complementary feature to clinical scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Our comparison group was selected and screened from a significantly younger population so as to avoid asymptomatic tears. Previous studies have shown a prevalence of asymptomatic tears in older populations [25,26]. Hawkes et al performed a comparison of muscle activation between RC and healthy groups with an age difference similar to that in our groups.…”
Section: Discussionsupporting
confidence: 66%
“…Our comparison group was selected and screened from a significantly younger population so as to avoid asymptomatic tears. Previous studies have shown a prevalence of asymptomatic tears in older populations [25,26]. Hawkes et al performed a comparison of muscle activation between RC and healthy groups with an age difference similar to that in our groups.…”
Section: Discussionsupporting
confidence: 66%
“…Quantitative evaluation of arm usage and quality of movements in every kind of shoulder impairment contributes to outline a clinical picture about the functional recovery and the effectiveness of the treatment [30, 49]. Using the same number of IMU ( n = 3) and the same placement on both humeri and sternum, the shoulder function was evaluated before and after treatment, in patients underwent surgery for RC tear [5, 34]. Results showed significative differences in movements frequency between patients and control group during activities of daily life [5], with limited use of arm at 3 months after surgery [34].…”
Section: Discussionmentioning
confidence: 99%
“…Using the same number of IMU ( n = 3) and the same placement on both humeri and sternum, the shoulder function was evaluated before and after treatment, in patients underwent surgery for RC tear [5, 34]. Results showed significative differences in movements frequency between patients and control group during activities of daily life [5], with limited use of arm at 3 months after surgery [34]. With a bilateral configuration based on 5 IMU, shoulder motion was assessed to extrapolate relevant clinical outcomes about Total Shoulder Arthroplasty (TSA) and Reverse Total Shoulder Arthroplasty (RTSA) [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting data provide a wealth of additional data points, may decrease the need for follow-up visits, and may serve as a base for complex data processing such as movement pattern analyses. Successful applications include quantification of significant changes in gait quantity and quality under a constrained environment [7], recovery of shoulder function after rotator cuff repair [8] and prediction of falls with accelerometry-based balance quantification [9]. The combination with either data such as vital signs but also positioning data adds meaning to the pure biomechanical data.…”
Section: Digital Biomarkers In Musculoskeletal Trialsmentioning
confidence: 99%